Intrahepatic cholangiocarcinoma with extensive intraductal extension of high-grade biliary intraepithelial neoplasia: a case report - Haruna Kubota; Yasushi Hashimoto; Kazuhiro Toyota; Raita Yano; Hironori Kobayashi; Yujiro Yokoyama; Yoshihiro Sakashita; Kiyomi Taniyama; Katsunari Miyamoto; Yoshiaki Murakami (Surgical Case Reports)
Abstract Background Intrahepatic cholangiocarcinoma (ICC) is frequently associated with precursor lesions, and biliary intraepithelial neoplasia (BilIN) may play a significant role in the development of ICC. However, the exact sequence and progression of these lesions remain to be elucidated. We report a rare case of ICC that exhibited extensive longitudinal intraductal extension of high-grade BilIN in the posterior bile ducts and involved the hepatic hilum and the peripheral hepatic parenchyma. Case presentation A 70-year-old female presented with anorexia. Computed tomography (CT) revealed a 15 mm enhancing intrahepatic tumor extending to the right intrahepatic secondary confluence. This was associated with a 7 mm diameter cystic dilatation of the segment 6 bile duct (B6). Endoscopic retrograde cholangiopancreatography (ERCP) revealed stenosis at the bifurcation of the posterior bile duct branch. Bile cytology confirmed the diagnosis of adenocarcinoma cells. Therefore, the patient was diagnosed with an ICC involving the right glissonean pedicle and underwent a right hepatectomy and lymph node dissection. Histologic examination revealed the tumor consisted of moderately differentiated adenocarcinoma. In connection with this lesion, diffuse intraductal atypical epithelial cells, which were diagnosed as high-grade BilIN, was observed not only in the dilated B6 but in the entire posterior bile ducts, which measured approximately 120 mm in diameter. Furthermore, two distinct foci of adenocarcinomas were identified in the peripheral hepatic parenchyma. A lymph node metastasis was also present. The pathological diagnosis was ICC pT4N1M0 stage IVA. The patient underwent adjuvant chemotherapy and has shown no recurrence 5 years after surgery. Imaging modalities were unable to accurately assess the extent of the intraductal neoplastic lesions due to their low papillary or sessile intraductal tubular growth. No risk factors for BilIN development, which has the potential to predispose to cholangiocarcinoma, were identified in the present case. Conclusions We present a case of ICC involving the right hepatic hilum, accompanied by extensive longitudinal extensions of high-grade BilIN and multifocal microscopic invasions in peripheral hepatic parenchyma. Notably, the intraductal lesions involved the entire posterior intrahepatic bile ducts. The presence of biliary neoplasia with extensive intraductal extension, in conjunction with ICC, should be considered as a variant of BilIN.